Workshop report: 28th Nordic workshop on bibliometrics and research policy, October 11–13, 2023, Gothenburg, Sweden - A. I. M. Jakaria Rahman; Marco Schirone; P. Anders Friberg; Cecilia Granell (Information Research: An International Electronic Journal)
The Nordic workshop on bibliometrics and research policy has been an annual event for almost three decades, rotating between the Nordic countries. It is a forum for the bibliometrics community to discuss contemporary research practices and policies. The 28th edition of the workshop took place in Gothenburg, Sweden. Featuring 27 oral and 15 poster presentations authored by 104 individuals, this event attracted 119 attendees from 19 countries. The event helped the participants to enhance their knowledge and engage with their peers. This workshop report offers insights into the pre-workshop sessions and provides an overview of the oral presentations across eight thematic sessions, keynote speeches, panel discussions, and poster sessions. Additionally, it includes references with links to presentations, posters, the book of abstracts, recording of keynote speeches and panel discussion.